Medicinal gardens as an educational strategy in the teaching of the natural sciences: A pedagogical proposal - Adriana-Elizabeth Reyes; Jorge-Manuel Dueñas (Research in Social Sciences and Technology- OpenED Network, 2021)
The main aim of this paper was to analyze how medicinal gardens in secondary schools can improve teaching-learning processes in rural settings. The sample comprised 179 students (69.3% girls) from a rural public secondary school in the province of Huila (Colombia). The age of the participants ranged from 15 to 17 years with a mean of 15.86 years (SD = 0.86). Seeking school motivation strategies for rural students from a rural institution in the municipality of Guadalupe, teachers of the natural sciences designed didactic-pedagogical alternatives employing situated learning that would allow them to contribute to solving school problems and environmental issues affecting rural areas. The environmental phenomena included the loss of fertile soils and the harmful effects of the use of agrochemicals. Medicinal gardens together with situated learning activities proved a useful teaching tool in formal rural educational settings.